Pelaksanaan Pembatalan Lelang Eksekusi Hak Tanggungan Atas Dasar Perbuatan Melawan Hukum - Muhamad Rizaldi Salas; Raden Khemal Hadda Sudjadiningrat; Ummi Maskanah (JURNAL ILMIAH LIVING LAW, 2025)
The cancellation of the auction caused many parties to suffer losses because they had promoted the auctioned goods and if they had been purchased, the sale and purchase transaction would be canceled. In decision No. 478 K/Pid/2013, there was a cancellation of the auction against the mortgage right. The study aims to determine and analyze the cancellation of the execution auction against the mortgage right due to an unlawful act. This study is a normative legal study, namely a study that examines norms as an object of research. The results of the study indicate that the lawsuit against the execution of the mortgage right does not cancel the auction because it can cause other legal problems, namely the cancellation of the sale and purchase transaction of the auctioned goods. Every decision that already has permanent legal force and is executed cannot be canceled. Therefore, every decision that results in other transactions must be ensured that there is no longer a legal process. And or execution must not be carried out before the end of the time given to the losing party to make legal efforts in the form of an appeal to cassation. The legal consequences of a court decision regarding the postponement or cancellation of the auction are the existence of legal uncertainty regarding the court's decision, harming the party conducting the auction, harming the party conducting the sale and purchase transaction of the auction object.